Protective and Regenerative Roles of T Cells in Central Nervous System Disorders - Evans, Frances L.; Dittmer, Marie; de la Fuente, Alerie G.; Fitzgerald, Denise C. (Frontiers in Immunology, 2019)
Pathogenic mechanisms of T cells in several Central Nervous System (CNS) disorders are well established. However, more recent studies have uncovered compelling beneficial roles of T cells in neurological diseases, ranging from tissue protection to regeneration. These divergent functions arise due to the diversity of T cell subsets, particularly CD4+ T cells. Here, we review the beneficial impact of T cell subsets in a range of neuroinflammatory and neurodegenerative diseases including multiple sclerosis, Alzheimer’s disease, Parkinson’s disease, amyotrophic lateral sclerosis, stroke and CNS trauma. Both T cell-secreted mediators and direct cell contact-dependent mechanisms deliver neuroprotective, neuroregenerative and immunomodulatory signals in these settings. Understanding the molecular details of these beneficial T cell mechanisms will provide novel targets for therapeutic exploitation that can be applied to a range of neurological disorders.